Private High School Reopened—COVID Mitigation and Clinical Surveillance Using an Internet Application. Issue 1 (January 2022) - Bellin, Eran; Elkin, Avigayil H.; Stiefel, Laurence; Shteingart, Lea; Infield, Mark; Nemetski, Sondra Maureen
Abstract : Context: Recommendations for COVID-safe, in-person, high school education have included masks and distancing between students but do not describe a scalable surveillance solution to rapidly identify and mitigate disease prevalence or exposure. Methods: Through an Internet application, all school participants reported symptoms, illness, or exposure daily. Physician-supervised follow-up interviews were reviewed and recorded in daily rounds. Students and faculty were allowed or prohibited to enter school based on the results. Results: From August 30, 2020, until April 13, 2021, a high school in Bergen County, New Jersey (an epicenter of high COVID prevalence), with 889 students and 214 faculty members, staff, and volunteers, generated 1497 assessments. Reasons for initial evaluation included 48 (3%) participants with positive COVID tests, 520 (34%) COVID-exposed, 178 (12%) exposed to someone with symptoms and unknown COVID status, 208 (14%) subjects with symptoms themselves, 525 (35%) exposed to a high-risk geography or air travel, and 12 (1%) contacts of a contact. Of the 61 subjects ultimately diagnosed with COVID, the sources of infection were 36 (57%) home exposure, 16 (27%) confirmed nonschool sources, 8 (13%) unknown, 1 (2%) travel to a high-risk area, and only one potential case of in-school transmission. Conclusions: Masks, distance, and aggressive contact tracing supported by an Internet application with consistent application of quarantine protocols successfully permitted in-school education without COVID spread in a high prevalence environment. This finding remains important to guide safety measures should vaccine-resistant strains—or new pandemics—challenge us in the future. Abstract : Supplemental Digital Content is Available in the Text.